Long-term effects of an alcohol prevention program at licensed premises: a Swedish 20-year follow-up study - Tobias H. Elgán; Sven Andréasson; Johanna Gripenberg (Frontiers Media S.A., 2024)
BackgroundIn 1996, a multicomponent community-based alcohol prevention program in Responsible Beverage Service (RBS) targeting licensed premises was developed by STAD (Stockholm Prevents Alcohol and Drug Problems) and implemented in Stockholm, Sweden. The program consists of community mobilization and collaboration, training, and enforcement. Early evaluations have shown a significant increase in the refusal rates of alcohol service to intoxicated patrons, from 5% in 1996 to 70% in 2001, and a 29% decrease in the frequency of police-reported violence. A cost-effectiveness analysis showed a cost-saving ratio of 1:39. The program was institutionalized by a collaborative steering group consisting of community stakeholders. This study aimed to evaluate the long-term effects over 20 years of the RBS program. The indicator chosen was the rate of alcohol overserving to obviously intoxicated patrons at licensed premises in Stockholm.MethodsA 20-year follow-up study was conducted using the same procedure as the baseline and previous follow-ups. Professional male actors (pseudopatrons) were trained by an expert panel to enact a standardized scene of obvious alcohol-intoxication. In 2016, 146 licensed premises located in the central part of Stockholm were randomly selected and visited. A review of program implementation from its initiation 1996 was conducted, examining critical events, including commitment from key actors in the community, training of bar staff, and enforcement.ResultsAt the 20-year follow-up, pseudopatrons were refused alcohol service in 76.7% of the attempts, which was at the same level (70%) as in the follow-up in 2001, thus indicating sustained effects of the RBS program. Compared with previous follow-ups, serving staff used more active intervention techniques in 2016 toward intoxicated patrons, such as refusing to take the order (56.9% in 2016 vs. 42.0% in 2001), and fewer passive techniques, such as ignoring patrons (6.5% in 2016 vs. 15.5% in 1999) or contacting a colleague (4.1% in 2016 vs. 25% in 2001).ConclusionThe sustained long-term effects of the RBS program are unique and can be explained by the high level of institutionalization of the multicomponent program, which is still ongoing in Stockholm. These findings can inform the dissemination of the program to other countries and settings.